Interaksi Antara Dunia Digital dan Fisik: Pemanfaatan Teknologi Simulasi Digital dan Cetak 3D (Yayasan Kawanad, 2023)
Digital simulation technology and 3D printing have eliminated the boundaries between the digital and physical world in the current digital era. This article aims to explore the increasingly close integration between the two domains through the use of digital simulation technology and 3D print. This research explores the application of this technology in various industrial sectors, examines the benefits offered, and identify the challenges faced in the implementation process. Literature study methods and secondary data analysis are used to present a comprehensive picture of the development of digital simulation and 3D print technology. This technology not only accelerates the design and production process, but also increases operational efficiency and encourages innovation in various industrial fields. This study reveals technology adoption by the manufacturing sector for fast prototyping and its important role in education to increase student involvement. Despite its various benefits, the implementation of this technology faces significant challenges such as high initial costs and resistance to change. However, with sustainable research and development and expanding industrial capacity, the potential of digital simulation technology and 3D print to improve innovation and future efficiency remains large. In conclusion, this article highlights the crucial role of digital simulation technology and 3D print in connecting the digital and physical world. By continuing to explore new applications and overcome existing challenges, it can be created a future where this technology not only supports industrial progress, but also strengthens the integration between virtual and physical reality faced today.